Adaptation and local knowledge of the Marind Anim Tribes in the utilization of Paperbark trees (Melaleuca leucadendron) in Merauke, South Papua, Indonesia - SUHARNO SUHARNO; AKHMAD KADIR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suharno, Kadir A. 2023. Adaptation and local knowledge of the Marind Anim Tribes in the utilization of Paperbark trees (Melaleuca leucadendron) in Merauke, South Papua, Indonesia. Biodiversitas 24: 6323-6331. Papuan rainforests are one of the most immensely diverse in the world. Such rich biodiversity provides a source of livelihood for the inland communities in Merauke, South Papua Province. For example, Paperbark trees (Melaleuca leucadendron) or kayu bus in the local language, which grow dominantly in lowland areas, are essential for the lives of the local inhabitants, the Marind Anim tribe. This research aims to elaborate on the use of Paperbark trees (M. leucadendron) by the Marind Anim tribe in their daily lives. Data were collected from surveys, interviews, and field observations. The interviews were conducted in multiple locations: Merauke, Sota, Muting, Semangga, and Tanah Miring. The results show that all members of the Marind Anim tribe (100%) depend on Paperbark for their livelihood, especially for the need for housing. The community has been using Paperbark trunks for house frames (92.31%), either unprocessed or in the forms of wooden blocks (5 x 5, 5 x 10, 10 x 10 cm) and boards (2 x 20 cm). They also utilize the wood for firewood. Other tribe members, i.e., the residents of the Wasur National Park, extract essential oils from Paperbark leaves. This utilization receives assistance and support from the area manager of the national park. Other than that, the community also utilizes the bark for house roofs, mats for crops, and firewood. In brief, the community's dependence on Paperbark trees is high because, other than being versatile, they are endemic to the lowland areas of Merauke, dominating other tree species. The findings suggest the importance of establishing a sound management system for the utilization of Paperbark trees to maintain sustainability in meeting the needs of surrounding communities.